A New Wave of Terrorism?: a Comparative Analysis of the Rise of Far-Right Terrorism - Collins, Jonathan (Perspectives on terrorism, 2021)
Far-right terrorist incidents are proliferating throughout the Western world. There has been an exponential increase in such incidents in the past ten years. To better understand this phenomenon, the author uses David Rapoport’s seminal theory on Modern Waves of Terrorism. Applying Rapoport’s measurement criteria, this article seeks to determine whether the increase in far-right violence constitutes a new terrorist wave. The study provides an extensive analysis using the Global Terrorism Database, linking research dedicated to comprehending domestic occurrences of far-right extremism with patterns and themes across the affected regions. Based on mixed-methods empirical analysis, this article contends that the data’s common themes and patterns fulfill Rapoport’s distinctive wave conditions with regard to the phenomenon’s international nature, the type of terrorist activity, its prompting cause, and its predominant energy.